Factors affecting the Adoption of Improved Management Practices of Mandarin in Gorkha, Nepal - Poudel, A.; Panth, B. P.; Karki, M.; Panta, H. K. (Journal of the Institute of Agriculture and Animal Science, 2020)
Gorkha is one of the leading mandarin producing districts located on the Hilly ecological belt in the north south of Nepal. The general objective the research was to assess adoption level of improved orchard practices of mandarin recommended through PMAMP which has high scope to improvise farming practices and mandarin productivity. Household survey was conducted at the major citrus producing wards of Gorkha Municipality and Sahid Lakhan Rural Municipality of Gorkha. Primary data were collected by the use of pretested interview questionnaire from 120 respondents selected at random to represent farmers of mandarin zone area. Data were processed and analyzed by using descriptive and inferential statistics through Ms-excel and SPSS. Chi-square tested the significant difference between independent and dependent variables. The analysis showed that majority of the respondents were middle age group, male, literate, had medium family size and medium level of income. Majority of them were affiliated to the farmers’ groups but lacked training. Majority of the respondents had medium level adoption of improved orchard management practices of mandarin. Among the socio-demographic parameters observed, significant relationship was found in case of age, education, membership in farmer’s group/organization, training and extension contact. Lack of knowledge and irrigation facility, insect-pest and disease problem and climatic uncertainty are the major problems in mandarin production. The medium scale farmers should be intervened by planners and extension agents for improving farming practices and productivity of mandarin provided with input resources.